2019
DOI: 10.1111/den.13423
|View full text |Cite
|
Sign up to set email alerts
|

Early feeding after esophageal variceal band ligation in cirrhotics is safe: Randomized controlled trial

Abstract: Background and Aim Oral feeding following variceal ligation in cirrhotics is usually delayed due to fear of rebleeding. Solid diet is usually further delayed (until 72 h) despite lack of evidence. We aimed to compare the impact of early versus delayed feeding on rebleeding following variceal ligation. Methods This was a prospective randomized controlled trial including patients undergoing variceal ligation for active esophageal variceal bleeding. Patients were randomized into two groups. In the early‐feeding g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
1
13
2
Order By: Relevance
“…[30][31][32] Optimal sedation during therapeutic endoscopic procedures provides good treatment outcomes and promotes patient satisfaction. [33][34][35][36][37] Nevertheless, some endoscopists hesitate to use sedation during emergency endoscopy for gastrointestinal bleeding because of fear of potential adverse events related to sedatives, such as respiratory depression and cardiovascular instability. 38 Sedation may prevent early resuscitation because it interferes with evaluation of mental status during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Optimal sedation during therapeutic endoscopic procedures provides good treatment outcomes and promotes patient satisfaction. [33][34][35][36][37] Nevertheless, some endoscopists hesitate to use sedation during emergency endoscopy for gastrointestinal bleeding because of fear of potential adverse events related to sedatives, such as respiratory depression and cardiovascular instability. 38 Sedation may prevent early resuscitation because it interferes with evaluation of mental status during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In most trials included in the current study, a liquid diet was initiated within 24 h, followed by a solid diet; however, in the study by Hepworth et al, 14 patients with bleeding peptic ulcers began solid diets immediately following endoscopic hemostasis. Moreover, Sidhu et al 7 suggested that beginning a solid diet 4 h after EVL was safe for patients with acute variceal bleeding. In addition, Miyakawa et al 20 suggested that an early solid diet could improve the satisfaction of patients who Figure 3 Comparison of postprocedural bleeding rate within 7 days between the early and delayed feeding groups.…”
Section: Discussionmentioning
confidence: 99%
“…In unstable patients and patients with endoscopic findings predictive of a high risk of rebleeding, feeding should be delayed. An RCT showed that early feeding with a regular solid diet in patients after successful variceal ligation for esophageal varices is safe, provides better nutrition, and results in a lower incidence of infections in bleeders compared to delayed feeding [224]. The results are promising, however, they included only patients with lowrisk varices.…”
Section: Grade Of Recommendation B E Strong Consensus (935% Agreement)mentioning
confidence: 99%